Are one-year changes in adherence to the 24-hour movement guidelines associated with depressive symptoms among youth? - Karen A. Patte; Guy Faulkner; Wei Qian; Markus Duncan; Scott T. Leatherdale (BMC, 2020)
Abstract Background There remains a need for prospective research examining movement behaviours in the prevention and management of mental illness. This study examined whether changes in adherence to the 24-h Movement Guidelines (moderate-to-vigorous physical activity [MVPA], sleep duration, screen time) were associated with depression symptoms among youth. Methods Conditional change models were used to analyze two waves of longitudinal questionnaire data (2016/17, 2017/18) from students in grades 9-12 (N = 2292) attending 12 schools in Ontario and British Columbia, Canada, as part of the COMPASS study. One-year change in adherence to the MVPA, screen time, and sleep duration guidelines were modeled as predictors of depressive symptoms, adjusting for covariates and prior year depressive symptoms. Models were stratified by sex. Results Continued adherence to sleep guidelines and transitioning from inadequate to sufficient sleep were associated with lower depressive symptoms than continued nonadherence, and continued adherence was associated with lower depression than transitioning from sufficient to short sleep. For screen time, transitioning from exceeding guidelines to guideline adherence was associated with lower depressive symptoms than continued nonadherence. MVPA guideline adherence was not associated with depression scores, when controlling for sleep and screen time guideline adherence change and covariates. When combined, meeting additional guidelines than the year prior was associated with lower depressive symptoms among females only. Conclusions Adherence to the sleep guidelines emerged as the most consistent predictor of depression symptoms. Promoting adherence to the Movement Guidelines, particularly sleep, should be considered priorities for youth mental health at a population level.